2020
DOI: 10.1159/000506688
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy Overweight and Obesity Are Associated with an Increased Risk of Preterm Birth in Chinese Women

Abstract: Introduction: The association between obesity before pregnancy and preterm birth varies with age and ethnicity. Objective: To study the association between early body mass index (BMI) and risk of preterm birth in Chinese women. Methods: This was a hospital-based retrospective cohort study including 36,596 Chinese women who gave birth to a live singleton infant from 2015 to 2018. Women were classified as underweight (BMI < 18.5), normal weight (BMI 18.5 to < 23), overweight (BMI 23 to < 27.5), or obese (BMI ≥27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 31 publications
(31 reference statements)
4
17
0
3
Order By: Relevance
“…However, this association has dramatically changed in a subgroup analysis of gestational age (table 3). Our result regarding extremely PTB is consistent with a previous study (Su et al 2020). Overweight and obesity are generally considered to be the risk factors for PTB due to the effects of placental insufficiency (Lassance et al 2015;Pereira et al 2015), inflammatory state (Gaillard et al 2016), insulin sensitivity (Catalano et al 1999) and cellular oxidative stress (Ballesteros-Guzman et al 2019).…”
Section: Ptbsupporting
confidence: 92%
See 1 more Smart Citation
“…However, this association has dramatically changed in a subgroup analysis of gestational age (table 3). Our result regarding extremely PTB is consistent with a previous study (Su et al 2020). Overweight and obesity are generally considered to be the risk factors for PTB due to the effects of placental insufficiency (Lassance et al 2015;Pereira et al 2015), inflammatory state (Gaillard et al 2016), insulin sensitivity (Catalano et al 1999) and cellular oxidative stress (Ballesteros-Guzman et al 2019).…”
Section: Ptbsupporting
confidence: 92%
“…Different countries, regions and incomes have different patterns of overweight and obesity that is more common among women in developing countries and men in developed countries (Ng et al 2014). Moreover, epidemiological studies have been suggested that maternal overweight and obesity have been shown to be association with PTB (Lynch et al 2014;Shaw et al 2014;Su et al 2020), LBW (Rahman et al 2015) and adverse maternal health PeerJ reviewing PDF | (2020:04:47383:2:0:NEW 10 Sep 2020)…”
Section: Introductionmentioning
confidence: 99%
“…The research that has been conducted is inconclusive – for example, Aly et al (2010) , in their retrospective study, analysed data from mothers who gave birth at the George Washington University between 1992 and 2003; they found that there was no link between maternal obesity and prematurity. However, Su et al (2020) also conducted a retrospective study of Chinese women who delivered between 2015 and 2018; the authors concluded that there was an increased risk of premature birth with maternal obesity, recommending weight loss prior to conception. In summary, maternal obesity may be a predisposing factor to prematurity; in view of this, mothers-to-be should be encouraged to maintain a healthy weight.…”
Section: Maternal Diseasementioning
confidence: 99%
“…33,34 Studies by Doi et al, Su et al, Castillejos et al, and Melchor et al also endorses similar results. 29,[30][31][32]35…”
Section: Resultsmentioning
confidence: 99%